A greener house : the sustainable property investor's guide to buying, building and renovating - Reed, Richard, 1963- (John Wiley and Sons, 2008)
"Sustainability is now an integral part of society and the built environment. Unfortunately many home owners and home-buyers are unaware of the relationship between sustainability and value, especially with regard to the potential added value to their home. Payback periods can be different depending on factors such as the initial capital outlay and the levels of depreciation and obsolescence, as well as savings made (if any) to the running costs of the home." -- Provided by publisher.